A systematic literature review on the components for designing and developing critical reading modules for EFL learners - Dongmei He; Asmaa AlSaqqaf (Human Resource Management Academic Research Society, 2024)
Teaching methods focusing on developing critical reading skills in English as a Foreign Language (EFL) contexts have gained popularity. However, effectively implementing these skills depends on clear knowledge, mastering understanding, and teacher readiness. Unfortunately, teachers often do not fully use effective approaches when teaching critical reading, making it difficult to integrate them into teaching reading. While there have been many studies on teaching critical reading skills, there are a few comprehensive reviews regarding the components of critical reading module. This article aims to identify the components of the critical reading skills teaching and learning module for EFL learners. By conducting a systematic literature review, this study uses Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) as the research framework. After reviewing 15 articles from 2018 to 2023, four themes were identified: module structure, module strategy, incorporating critical thinking, and module content. The study suggests that these themes are essential for teaching critical reading in the EFL context. It provides valuable guidance for teachers and opportunities for students to learn through critical reading skills.